ALKBH5 Regulates SPHK1-Dependent Endothelial Cell Angiogenesis Following Ischemic Stress - Kumari, Rajesh; Dutta, Roshan; Ranjan, Prabhat; Suleiman, Zainab Gbongbo; Goswami, Sumanta Kumar; Li, Jing; Pal, Harish Chandra; Verma, Suresh Kumar (Frontiers in Cardiovascular Medicine, 2022)
Background Endothelial cells dysfunction has been reported in many heart diseases including acute myocardial infarction, and atherosclerosis. The molecular mechanism for endothelial dysfunction in the heart is still not clearly understood. We aimed to study the role of m6A RNA demethylase alkB homolog 5 (ALKBH5) in ECs angiogenesis during ischemic injury. Methods and Results ECs were treated with ischemic insults (lipopolysaccharide and 1% hypoxia) to determine the role of ALKBH5 in ECs angiogenesis. siRNA mediated ALKBH5 gene silencing was used for examining the loss of function. In this study, we report that ALKBH5 levels are upregulated following ischemia and are associated with maintaining ischemia-induced ECs angiogenesis. To decipher the mechanism of action, we found that ALKBH5 is required to maintain eNOS phosphorylation and SPHK1 protein levels. ALKBH5 silencing alone or with ischemic stress significantly increased SPHK1 m6A mRNA methylation. In contrast, METTL3 (RNA methyltransferase) overexpression resulted in the reduced expression of SPHK1. Conclusion We reported that ALKBH5 helps in the maintenance of angiogenesis in endothelial cells following acute ischemic stress via reduced SPHK1 m6A methylation and downstream eNOS-AKT signaling.